An Overview on Food Applications of the Instant Controlled Pressure-Drop Technology, an Innovative High Pressure-Short Time Process - Juan Leopoldo Pech-Almeida (MDPI AG, 2021)
Food processing systematically aims at meeting the needs of consumers who are looking for total high quality and perfect food safety. As the various thermal and non-thermal food preservation technologies often affect the natural properties in terms of sensation, flavor, texture, etc., instant controlled pressure drop (DIC) has been conceived as a relevant, innovative process in this field. DIC uses high saturated steam pressure and short duration to provide a new way to expand biological matrices, improve drying, decontaminate, and extract biologically active compounds, among other attributes. Therefore, this review focuses on describing the applications of DIC technology on a wide range of products such as foods and by-products that have been processed both in the laboratory and on an industrial scale. The application of DIC has shown the possibility of a significant leap in quality improvement and cost reduction in the food industry. DIC reduces the drying time of fruits and vegetables, and improves the extraction of essential oils, vegetable oils, and antioxidant components. It also provides strong decontamination, eliminates vegetative microorganisms and spores, and reduces non-nutritional and allergenic components. Over the past 33 years, this technology has continued to expand its food applications and improve its characteristics on an industrial scale. But there are still many food unit operations that can be taken to the next level with DIC.